The E-Shopper’s Journey: Examining the Role of Engagement in Online Retail Success - K. S., Giridharan (International Journal of Psychosocial Rehabilitation, 2016)
In the rapidly evolving digital marketplace, consumers are increasingly gravitating towards online shopping, drawn by the convenience and wealth of information it offers. Despite its growing popularity, there remain significant hurdles that online retailers must overcome to ensure a seamless and satisfactory customer experience. To delve deeper into the effectiveness of online retail strategies, a comprehensive study was conducted focusing on customer engagement and its subsequent effect on purchase intentions and brand loyalty. This research targeted 416 experienced online shoppers in Chennai, seeking to understand their perceptions and predicted behaviors in response to online retail tactics. The study utilized rigorous regression analysis on the collected primary data to uncover nuanced insights into the dynamics of online customer engagement. The findings reveal critical factors that influence consumers’ willingness to continue purchasing from an online platform and their propensity to develop loyalty towards a digital retailer. These insights are crucial for online retailers aiming to refine their engagement strategies to foster long-term customer relationships. By highlighting key drivers of consumer satisfaction and loyalty, the study offers valuable guidelines for enhancing online shopping experiences and shaping future marketing approaches in the domain of e-commerce.